Transverse momentum dependence of inclusive primary charged-particle production in p–Pb collisions at √sNN=5.02 TeV - Abelev, B.; Adam, J.; Adamovã, D.; Aggarwal, M.M.; Agnello, M.; Agostinelli, A.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahmed, I.; Ahn, S.U.; Ahn, S.A.; et al. (Springer New York LLC, 2014)
The transverse momentum (pT) distribution of primary charged particles is measured at midrapidity in minimum-bias p–Pb collisions at √sNN = 5.02 TeV with the ALICE detector at the LHC in the range 0.15 < pT < 50 GeV/c. The spectra are compared to the expectation based on binary collision scaling of particle production in pp collisions, leading to a nuclear modification factor consistent with unity for pT larger than 2 GeV/c, with a weak indication of a Cronin-like enhancement for pT around 4 GeV/c. The measurement is compared to theoretical calculations and to data in Pb–Pb collisions at √sNN = 2.76 TeV.
Keywords: Physics; Spectral line; Charged particle; Production (economics); Particle physics; Large Hadron Collider; Nuclear physics; Scaling; Particle identification; Range (aeronautics); Detector; Ion; Geometry; https://purl.org/pe-repo/ocde/ford#1.03.04